(3JMbjb GdfUQI aj JdNjU eYGde GdgLQIs - (3CHh HcQ (B((3YHO Gddg(B) (3Hf GdMSjf Hf YeQ, CHh eMeO GdeUQj GdTGaYqj GdeQGZj GdbQTj, Rjf GdOjf,J (B816 (3g` s ((3YHO Gddg Hf YHO GdcGai Hf Ydi GdMSfi GdWHGWHj s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdeOjfI GdTQjaI OGQ gLQI QShdg CdN s
(3BNQgG (B:s
(3bGd eDdag YaG Gddg Yfg (B: (3aQZJ ef JHjjVg jhe GdSHJ (B12 (3QLH s
(3fSNI KGdKIs
(3hgh ai JGQjN GdeOjfI GdefhQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B60s
Keywords: (3GdJGQjNs